Rollout Strategy to Implement Interoperable Traceability in the Seafood Industry. (August 2017) - Gooch, Martin; Dent, Benjamin; Sylvia, Gilbert; Cusack, Christopher
Abstract: Verifying the accuracy and rigor of data exchanged within and between businesses for the purposes of traceability rests on the existence of effective and efficient interoperable information systems that meet users' needs. Interoperability, particularly given the complexities intrinsic to the seafood industry, requires that the systems used by businesses operating along the supply chain share a common technology architecture that is robust, resilient, and evolves as industry needs change. Technology architectures are developed through engaging industry stakeholders in understanding why an architecture is required, the benefits provided to the industry and individual businesses and supply chains, and how the architecture will translate into practical results. This article begins by reiterating the benefits that the global seafood industry can capture by implementing interoperable chain‐length traceability and the reason for basing the architecture on a peer‐to‐peer networked database concept versus more traditional centralized or linear approaches. A summary of capabilities that already exist within the seafood industry that the proposed architecture uses is discussed; and a strategy for implementing the architecture is presented. The 6‐step strategy is presented in the form of a critical path.